Local language and cultural conflict in Flores Island Society. A Critical Linguistics Study on Cross Cultural Communication in the Middle of Cultural Conflict in Flores Island Society - Gobang, Jonas Klemens Gregorius Dori; Noang, Edmondus Iswenyo; Salesman, Frans (Technium Social Sciences Journal, 2021)
Flores Island is one of the diverse place despite its small size as the part of Indonesian East Archipelago and Lesser Sunda Island. We all know that regional language or local language is an intellectual and cultural property. Local language lives and develops in an area or community. There are many regional languages accustomed to be used as a means of communication. The use of local language with its different meanings in a region or community that is no longer homogeneous can be a trigger to cultural conflict. The causes of conflict among residents or cultural believers are assimilation and mixing of heterogeneous local language-speaking communities. This study aims at revealing the existence of cultural conflicts as a result of the meaning differences of local languagesused by the people on Flores Island. This study uses a critical linguistics approach with a cross-cultural communication paradigm.